CT fluoroscopy-guided percutaneous gastrostomy (CT-PG) – A single center experience in 233 patients. Issue 152 (July 2022) - Segger, Laura; Auer, Timo A.; Fleckenstein, Florian Nima; Fehrenbach, Uli; Torsello, Giovanni Federico; Frisch, Anne; Jonczyk, Martin; Hamm, Bernd; Gebauer, Bernhard
Abstract: Purpose: To investigate the feasibility and complications of computed tomography-guided percutaneous gastroscopy (CT-PG) using two procedural techniques (trocar technique and Seldinger technique) in all patients and in a subgroup of patients with ascites as a relative contraindication. Material and methods: In this single-center study a total of 233 patients who underwent CT-PG (55 in trocar group and 178 in Seldinger group) between 2012 and 2021 were analyzed retrospectively. Success and complications were determined for both techniques and compared in the total study population and in the subgroup of patients with ascites. Complications were classified using the Common Terminology Criteria for Adverse Events (CTCAE) Protocol for procedural complications. Results: Feeding tube placement was successful in 93.6% of cases (218/233). In the trocar group, placement was successful in 98.2% (54/55) with a complication rate of 7.4% (4/54) including one grade 5 complication. In the Seldinger group, placement was successful in 92.1% (164/178) with a complication rate of 6.7% but no grade 4 or 5 complication. Preprocedural paracentesis for ascites was performed in 6.9% of patients (16/233). In this subgroup, CT-PG was successful in 87.5% (14/16) and only complications rated as grade 1 or 2 occurred. Conclusion: CT-PG is a safe interventional procedure, which also applies to patients with ascites if paracentesis is performed beforehand. Specifically, our findings show the Seldinger technique to be safe, as no severe complications occurred in this subgroup.